Comparative analysis of differentially expressed sequence tags of sweet orange and mandarin infected with Xylella fastidiosa - Souza, Alessandra A. de; Takita, Marco A.; Coletta-Filho, Helvécio D.; Campos, Magnólia A.; Teixeira, Juliana E.C.; Targon, Maria Luísa P.N.; Carlos, Eduardo F.; Ravasi, Juliano F. [UNESP]; Fischer, Carlos N. [UNESP]; Machado, Marcos A. (Sociedade Brasileira de Genética, 2007)
The Citrus ESTs Sequencing Project (CitEST) conducted at Centro APTA Citros Sylvio Moreira/IAC has identified and catalogued ESTs representing a set of citrus genes expressed under relevant stress responses, including diseases such as citrus variegated chlorosis (CVC), caused by Xylella fastidiosa. All sweet orange (Citrus sinensis L. Osb.) varieties are susceptible to X. fastidiosa. on the other hand, mandarins (C. reticulata Blanco) are considered tolerant or resistant to the disease, although the bacterium can be sporadically detected within the trees, but no disease symptoms or economic losses are observed. To study their genetic responses to the presence of X. fastidiosa, we have compared EST libraries of leaf tissue of sweet orange Pêra IAC (highly susceptible cultivar to X. fastidiosa) and mandarin Ponkan (tolerant) artificially infected with the bacterium. Using an in silico differential display, 172 genes were found to be significantly differentially expressed in such conditions. Sweet orange presented an increase in expression of photosynthesis related genes that could reveal a strategy to counterbalance a possible lower photosynthetic activity resulting from early effects of the bacterial colonization in affected plants. on the other hand, mandarin showed an active multi-component defense response against the bacterium similar to the non-host resistance pattern.
Keywords: ESTs; citrus variegated chlorosis; biotic stress; CitEST; phytopathogen